2009
DOI: 10.1253/circj.cj-08-1076
|View full text |Cite
|
Sign up to set email alerts
|

Pocket-Sized Transthoracic Echocardiography Device for the Measurement of Cardiac Chamber Size and Function

Abstract: echnological advances in electronic miniaturization have resulted in the creation of small, portable transthoracic echocardiographic (pTTE) devices. The major advantage of a portable device is being able to provide immediate information both within and, for the first time, outside the hospital setting. Previous studies have reported that pTTE is superior to physical examination, and comparable with complete standard TTE (sTTE) as a diagnostic tool in clinical practice. 1-3 Physical examination is recognized as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 20 publications
2
53
1
1
Order By: Relevance
“…Although this study commented on the accuracy of PSE compared to sTTE in a subset of patients, this was not the primary objective. Image accuracy has been previously well described in various other patient populations [7][8][9][10][11][12][13][14][15][16][17][18]. Finally, although this study validated the use of PSE in assessing LVEF, if more extensive information on cardiac structure and function is required clinically prior to PPM implantation sTTE is superior to that of PSE.…”
Section: Limitations and Future Directionsmentioning
confidence: 51%
See 1 more Smart Citation
“…Although this study commented on the accuracy of PSE compared to sTTE in a subset of patients, this was not the primary objective. Image accuracy has been previously well described in various other patient populations [7][8][9][10][11][12][13][14][15][16][17][18]. Finally, although this study validated the use of PSE in assessing LVEF, if more extensive information on cardiac structure and function is required clinically prior to PPM implantation sTTE is superior to that of PSE.…”
Section: Limitations and Future Directionsmentioning
confidence: 51%
“…Its size confers the advantage of portability, making PSE ideal for point-of-care evaluation, either at the bedside, or in the outpatient setting. Previous studies have examined the diagnostic accuracy of PSE, its potential clinical applications, and the training involved to maximize safety and effectiveness of its use [7][8][9][10][11]. Several studies have reported that PSE can qualitatively assess LVEF with good reliability, even when a sonographic trainee acquires and/or interprets images [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies reported that HCU showed good concordance of diagnostic capability with SED in terms of assessing LVEF and LV dimension measurement and detecting pericardial effusion and valve disease (4)(5)(6)(7)(8)(9) . Also, they are being placed in emergency or critical care settings to assist in the evaluation of hemodynamically compromised patients (10)(11)(12) .…”
Section: Discussionmentioning
confidence: 84%
“…Left heart dimensions measured with Acuson P10 TM and Vscan V1.2 devices are accurate when compared to high-end echocardiography performed by experienced cardiologists [13,48]. Exportation of images to a full-size screen does not improve the accuracy of measurements or diagnosis, and real-time interpretation increases efficiency [16].…”
Section: Devices and Their Accuracymentioning
confidence: 99%